Silver nanowires intercalating Ti3C2Tx MXene composite films with excellent flexibility for electromagnetic interference shielding. Issue 9 (31st January 2020) - Miao, Miao; Liu, Ruiting; Thaiboonrod, Sineenat; Shi, Liyi; Cao, Shaomei; Zhang, Jianfeng; Fang, Jianhui; Feng, Xin
Abstract : Highly efficient EMI shielding composite films with excellent flexibility were fabricated by intercalating sliver nanowires into Ti3 C2 T x nanosheets using nanocellulose as a green binder. Abstract : Ultrathin, lightweight and flexible electromagnetic interference (EMI) shielding films are urgently desired for the next generation electronic devices with complex-shaped surfaces. In this study, flexible EMI shielding composite films were fabricated by intercalating sliver nanowires (AgNWs) into Ti3 C2 T x MXene nanosheets followed by a pressured-extrusion film-forming process. The resultant MXene/AgNW composite films with a low loading of nanocellulose (0.167 wt%) as a green binder exhibited remarkable conductivity (∼30 000 S m −1 ) and outstanding specific EMI shielding effectiveness (SSE/t, 16 724 dB). Thanks to the strengthening mechanism of the "brick-and-mortar" layered structure, the tensile stress of the MXene/AgNW composite film dramatically improved from 1.29 MPa (pure Ti3 C2 T x film) to 63.80 MPa, and the electric conductivity and EMI SE can be maintained even after bending at 135° 10 000 times. The MXene/AgNW hybrid films with excellent EMI SE and mechanical robustness offered promising applications in the fields of aerospace, defense, smart electronics and flexible/wearable devices.